Immune response and rational development of vaccines and biomarkers - Kaufmann, Stefan H. E. (Henry Stewart Talks, 2013)
Tuberculosis (TB), immune response and vaccine development, TB: a major health threat, T lymphocytes as central mediators of immunity in TB, Rational design of novel vaccines against TB, Characterization of biomarkers for TB vaccine trials